Self-care Management among Patients with Type 2 Diabetes Mellitus in Tanahun, Nepal - Baral, Ishwari Adhikari; Baral, Santosh (Archives of Community Medicine and Public Health, 2021)
Maintaining optimum blood glucose level in diabetic patients requires proper self-care management focusing on diet, medication, regular exercise, and foot care. The aim of the study was to investigate self-care practices and predictors of self-care management activities among type 2 diabetes mellitus patients in Tanahun district of Nepal. Methods: Descriptive cross- sectional study was carried out among 139 patients with type 2 diabetes mellitus attending outpatient department of two private polyclinics of Bhimad Municipality at Tanahun district, Nepal. The self-care practice was measured by the Summary of Diabetes Self-Care Activities (SDSCA). Predictors of self-care behaviors were identified by using binary logistic regression. Results: Among the 139 patients, less than half (46%) had desirable self-care practice for diabetes management. Of the total, 89.9% had adequate exercise and 74.8% and had foot care management practices. The multivariate analysis showed that poor self-care practice was likely to occur among illiterate patients (AOR=2.950; 95% CI= (1.149-7.573); p <0.05) and patients with co-morbidities (AOR=2.801; 95% CI=1.121-7.002; p <0.05). Conclusion: Self-care practice of diabetic participants was considerably particularly in practice of recommended blood glucose testing. These findings recommend health care organizations and professionals to plan on behavioral change communication and education programs targeting diabetic patients in order to improve their self-care practice.